Concentrations and emissions of trichlorotrifluoroethane (CFC-113) from eastern china inferred from atmospheric observations. (1st December 2022) - Yang, Yang; Li, Xinhe; Li, Bowei; Hu, Xiaoyi; Fang, Xuekun
Abstract: Trichlorotrifluoroethane (C2 Cl3 F3, CFC-113) is a long-lived ozone-depleting substance (ODS) regulated under the Montreal Protocol and a potent greenhouse gas (GHG). Production and consumption of chlorofluorocarbons (CFCs) were phased out after 2007 in China, while unexpected increases in CCl3 F (CFC-11) emissions from eastern China after 2012 were inferred from atmospheric observations. However, atmospheric concentrations and emissions of CFC-113 in China over the past few years are unclear. In this study, we conducted hourly observation of atmospheric CFC-113 concentrations in 2021 in eastern China, explored the potential CFC-113 emission sources using a dispersion model, and estimated the CFC-113 emissions using an interspecies correlation method. Results show that pollution events of CFC-113 were observed frequently, and the concentrations were higher than those of global background stations with similar latitudes. The dominant potential emission regions of CFC-113 were located in the eastern-central Yangtze River Delta region and Shandong province. The estimated mean CFC-113 emission from eastern China in 2021 was 0.88 ± 0.19 Gg/yr (5350 ± 1155 CO2 -equivalent Gg/yr), which was higher than 0 Gg/yr (0 CO2 -equivalent Gg/yr) in 2008−2021, as reported by bottom-up studies that considered CFC-113 to be phased out in China after 2007. Therefore, substantial CFC-113 emissions still existed in eastern China in 2021, which are of importance to protecting the ozone layer and mitigating the effects of climate change.